STUDENTS' PERCEPTION TOWARDS THE DIFFICULTY OF GRAMMATICAL FEATURES AT UIN ALAUDDIN MAKASSAR - Rahman, Indah Fadhilah; Asmawati, Andi; Elmayana, Elmayana (elstic : english language linguistics culture, 2024)
This research investigates how students perceive the difficulty of various grammatical features in the English language. Furthermore, the grammatical features in this research are based on the Semester Learning Plan (RPS) for the grammar subject. A quantitative approach was employed, utilizing survey research methodology with a sample of 70 students chosen through purposive sampling. The students' perceptions of twelve grammatical features were assessed using a Likert scale, ranging from “very easy” to “very difficult.” The results revealed diverse perceptions among students regarding the difficulty of these grammatical features, reflecting the complexity of language acquisition. Part of speech, modals, WH-Question, question tag, gerund, direct and indirect, degrees of comparison, and passive voice were perceived as not all difficult. Tenses, causative, infinitives, and conditional sentence were perceived as difficult. These findings underscore the importance of tailored teaching strategies and support to address students' varying perceptions of grammatical difficulty. This research contributes to the field of language education by shedding light on students' perspectives on the difficulty of various grammatical features, filling a gap in research on grammatical difficulty from the learners' viewpoint. The insights gained from this study can guide educators in adapting their teaching methods to better support students in mastering English grammar, ultimately improving their proficiency in the language and facilitating effective communication in both academic and real-world contexts.